Onset of clinical immunity to Plasmodium falciparum among Javanese migrants to Indonesian Papua. - Baird, J; Krisin; Barcus, M; Elyazar, I; Bangs, M; Maguire, J; Fryauff, D; Richie, T; Sekartuti; Kalalo, W (2003)
Onset of clinical immunity to Plasmodium falciparum occurred among Javanese migrants to Indonesian Papua. Surveillance of the 243 migrants investigated began on the day of their arrival in Indonesian Papua and continued for 33 months. Asexual parasitaemia without fever constituted objective evidence of clinical immunity. Compared with first infection, the odds ratio (OR) for not having fever at the fourth infection within 24 months was 3.2 [95% confidence interval (CI)=1.03-10.2; P=0.02]. The corresponding OR with fewer infections within 24 months was not distinguishable from 1.0. The level of the fourth parasitaemia within 24 months (N=58) was classified as 'high' or 'low' in relation to the median count at first infection (840 parasites/microl; N=187). Fourth parasitaemias that were low-but not those that were high (OR=1.8; CI=0.6-5.4; P=0.35)-were associated with dramatic protection from fever (OR=31; CI=3.5-1348; P=0.0001). Among the adult subjects, the risk of fever with low parasitaemia was significantly higher at the first infection than at the fourth (OR=12.6; CI=1.7-530; P=0.005), indicating the development of clinical immunity. A similar but less marked pattern appeared among the children investigated (OR=6.5; CI=0.8-285; P=0.06).